Ambient UV-B exposure reduces the binding of ofloxacin with bacterial DNA gyrase and induces DNA damage mediated apoptosis. (April 2016) - Singh, Jyoti; Dwivedi, Ashish; Mujtaba, Syed Faiz; Singh, Krishna P.; Pal, Manish Kumar; Chopra, Deepti; Goyal, Shruti; Srivastav, Ajeet K.; Dubey, Divya; Gupta, Shailendra K.; Haldar, Chandana; Ray, Ratan Singh
Graphical abstract: Highlights: OFLX generates two photoproducts after irradiation at ambient intensity of UV-B. Binding affinity of photosensitized OFLX with DNA gyrase attenuated. Photosensitized OFLX induced formation of micronuclei and CPDs. DNA damage and G1 phase cell cycle arrest and apoptosis. Upregulation of Bax, Cyt-c and Caspase-3 and downregulation of Bcl-2 proteins. Abstract: Ofloxacin (OFLX) is a broad spectrum antibiotic, which generates photo-products under sunlight exposure. Previous studies have failed to explain the attenuated anti-bacterial activity of OFLX. The study was extended to explore the unknown molecular mechanism of photogenotoxicity on human skin cell line (HaCaT) under environmental UV-B irradiation. Photochemically OFLX generates ROS and caused 2′-dGuO photodegradation. We have addressed the binding affinity of OFLX and its photo-products against DNA gyrase. Significant free radical generation such as 1 O2, O2 − and OH reduces antioxidants and demonstrated the ROS mediated OFLX phototoxicity. However, the formation of micronuclei and CPDs showed photogenotoxic potential of OFLX. OFLX induced cell cycle arrest in sub-G1 peak. OFLX triggers apoptosis via permeabilization of mitochondrial membrane with the downregulation of anti-apoptotic Bcl-2 and caspase-3 whereas, upregulation of pro-apoptotic Bax and Cyto- C proteins. Our study illustrated that binding affinity of OFLX photo-products with DNA gyrase was mainly responsible for the attenuated antimicrobial activity. It was proved through molecular docking study. Thus, study suggests that sunlight exposure should avoid by drug users especially during peak hours for their safety from photosensitivity. Clinicians may guide patients regarding the safer use of photosensitive drugs during treatment.